Simulasi Dampak Ledakan Supernova terhadap Planet Terdekat - Gomes, Margareth Jacoba Da; Sitanggang, Cesilia Uli Sondang; Gultom, Septi Maria; Situmorang, Howard; Wulandari, Dewi; Warty, Yuni (Mataram University, 2025)
This study aims to analyze the comparison of kinetic energy generated by five planets in the solar system and to visually simulate the supernova explosion process as a part of exploring cosmic energy dynamics. A quantitative computational method was employed using Python programming within the Visual Studio Code environment to calculate the kinetic energy of each planet based on its mass and orbital velocity. The data were presented on a logarithmic scale graph to clearly illustrate the wide range of energy magnitudes. The simulation results show that Jupiter generates the highest energy, approximately 3,39 × 1038 Joules, while Mercury yields the lowest, around 6,83× 1030 Joules. In addition to numerical analysis, this research includes a visual simulation of a supernova explosion to depict the dramatic transition of a massive star collapsing and releasing a tremendous amount of energy. The video illustrates the sequential phases of the explosion, including core collapse, shock wave formation, and the outward dispersal of stellar material represented by intense light bursts and dynamic color shifts. This visualization reinforces the understanding of the extreme energy scales involved in supernova events and their impact on the surrounding cosmic environment, including the possible formation of neutron stars or black holes. This study demonstrates how computational modeling and visual simulations can complement each other in explaining complex astrophysical phenomena and serve as an educational tool to enhance understanding of cosmic energy and stellar evolution.